Monitoring wellbeing during recovery from the 2010–2011 Canterbury earthquakes: The CERA wellbeing survey. (December 2015) - Morgan, Jane; Begg, Annabel; Beaven, Sarah; Schluter, Philip; Jamieson, Kath; Johal, Sarb; Johnston, David; Sparrow, Mary
Abstract: In this paper we outline the process and outcomes of a multi-agency, multi-sector research collaboration, led by the Canterbury Earthquake Recovery Authority (CERA). The CERA Wellbeing Survey (CWS) is a serial, cross-sectional survey that is to be repeated six-monthly (in April and September) into the foreseeable future. The survey gathers self-reported wellbeing data to supplement the monitoring of the social recovery undertaken through CERA's Canterbury Wellbeing Index. Thereby informing a range of relevant agency decision-making, the CWS was also intended to provide the community and other sectors with a broad indication of how the population is tracking in the recovery. The primary objective was to ensure that decision-making was appropriately informed, with the concurrent aim of compiling a robust dataset that is of value to future researchers, and to the wider, global hazard and disaster research endeavor. The paper begins with an outline of both the Canterbury earthquake sequence, and the research context informing this collaborative project, before reporting on the methodology and significant results to date. It concludes with a discussion of both the survey results, and the collaborative process through which it was developed.